'I gave someone a good death': Anonymity in a community of Reddit's medical professionals. (December 2020) - Henninger, Nicole M
Anonymity is often regarded as a negative influence on the quality of online communication, but can anonymity serve to bridge communication gaps under specific conditions? This study explores this question by examining key affordances of Reddit using a quasi-ethnographic method. Here, anonymity is combined with active norm enforcement by self-appointed moderators of subReddits. This study develops the concept of actively moderated anonymity and assesses its ability to mend gaps in communication through an online ethnography of Medicine, a Reddit community of self-identified medical professionals to answer the following: How does anonymity work as an affordance in shaping online discussions, such as those in r/medicine, and what types of exchanges are occurring between medical professionals in the r/medicine community that may not occur elsewhere? r/medicine's community provided a place for comfort and a place to freely exchange ideas including sensitive topics and opposing viewpoints. Findings conclude that medical professionals often sought to validate decisions they had made in the workplace and attempted to resolve concerns about particular institutional or systemic issues, suggesting actively moderated anonymity may afford an additional level of support that medical professionals may not find in the workplace or within an identifiable setting that could potentially be invaluable to the services provided to patients.